Is Morphine for Euthanasia? - Molek, Ruechuta; Thanapapothiwat, Tanyatorn; Kongchaiphome, Kanda; Sombutboon, Marisa; Preechakoon, Benjamas (The Journal of Chulabhorn Royal Academy, 2020)
All terminal stage, cancer patients are inevitable to confront the anguishing and agonizing pain from the diseases. The suffering of acute and chronic pain results in patients’ behavioral and physical changes as well as severe psychological stress. Morphine has been widely applied for pain relief on account of giving patient euphoria and relaxation. However, overconsumption may cause significantly physical complications in drug addict and respiratory depression. Therefore, application selection as well as an appropriate level of Morphine is an alternative to be considered for those cancer patients suffering at end stage and leaving peacefully. Morphine can rescue severe and despairing patients from treatment which is based on an appropriate concept and practice, law of the country, social custom and tradition according to religious doctrine and human dignity. However, Euthanasia legislation in Thailand has not been approved except in some countries where the stated laws have been accepted.